KONSTRUKSI MAKNA CADAR OLEH WANITA BERCADAR JAMAAH PENGAJIAN MASJID UMAR BIN KHATTAB KELURAHAN DELIMA KECAMATAN TAMPAN PEKANBARU - Mutiara Sukma Novri; Nova Yohana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Recently, the phenomenon of veiled women has become familiar in our society. in the region of pekanbaru the use of the veil by women followers of Islam also became a phenomenon in which there is an increase in terms of usage. It can be seen from the increasing proliferation of associations for women of Muslims who use the veil, one of which is the association of Umar bin Khattab mosque in the village of Delima. This study aims to determine how to construct meaning veiled women related motives, meanings and experiences of their everyday communication.This study uses qualitative research with phenomenological approach. Informants in this study were seven women veiled pilgrims recitals Umar selected purposively. Data collection techniques is done by observation, interview, and documentation. To achieve the validity of the data in this study, researchers used the extension of participation and triangulation.Results from this study showed that the motives of the women veiled mosque worshipers recitation Umar motifs past (Because motif) form the basis of religion because of the theological motifs that have been ingrained in them as well as the motives for keeping away from the view of men who are not mukhrim. While the motive of the future (in-order to) is to expect God’s blessing, being a woman sholehah, became motivation for others as well as to honor her husband. Making of veiled women to veil that they use is a religious order which they believe the law required and afdhol, they also wear the veil as a psychological need for self-control and to behave. Communication experience veiled women Umar bin Khattab mosque is a pleasant experience that comes from the support of his family and relatives, whereas an unpleasant experience covering the stigma of people who mocked and blasphemed as a member of terrorismKeywords: construction of meaning, veiled women, motives, meaning, experience communication